Konstruksi Model Pembelajaran Holistik-Eksperiensial: Integrasi Metode Tajribi dan Program Ngaji Rasa di Pesantren - Abu Warasy Batula; Nurlaila Turohmah; Robiatul Adawiyah Ramadhani; Antiti Armilah; Yahya Rafi Sya’bani (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
The digital era has introduced significant challenges in the form of educational degradation, where cognitive achievements are often prioritized over the internalization of moral-spiritual values. In Indonesia, Islamic boarding schools (pesantren) face serious constraints, with digital readiness levels as low as 16.4% and a curriculum dominated by classical text memorization, leading to insufficient critical thinking skills (6.2%). This study aims to construct a Holistic-Experiential learning model by integrating the Tajribi method and the Ngaji Rasa program as a strategic solution within the pesantren ecosystem. The research employs a qualitative method with a library research approach, utilizing content and thematic analysis for data interpretation. The findings reveal that the Tajribi method serves as a methodological foundation for experiential learning, while Ngaji Rasa acts as an affective manifestation implemented through a hidden curriculum. The construction of this model is epistemologically rooted in QS. Ash-Shaff: 2–3, which integrates ’ilm (knowledge), amal (action), and niyyah (intention). The novelty of this research lies in the inclusion of the spiritual dimension as a fourth pillar, transcending Bloom's taxonomy by forming a learning tetragonal that encompasses cognitive, affective, psychomotor, and spiritual domains. In conclusion, the integration of Tajribi and Ngaji Rasa transforms the pesantren into a "character laboratory" capable of bridging classical traditions with modernization demands without losing its spiritual identity.